Workplace Stress and Mental Health Challenges among Working Women (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Workplace stress and mental health issues specific to women have been on the rise in recent decades, coinciding with a marked increase in women's labour force involvement. This research delves into the many aspects of workplace stress experienced by women in various professions, including its causes, effects, and methods of coping. Using a combination of standardised stress and mental health questionnaires and semi-structured interviews, data was gathered from 200 participants using a mixed-methods approach. The most common causes of stress, according to the research, were an excessive workload, an unbalanced work-life relationship, gender bias, and a lack of support from inside the organisation. Married women who are also responsible for child care reported significantly greater levels of stress, burnout, and emotional tiredness compared to the overall participants. Organisational treatments are still limited and inconsistent, the report notes, in contrast to personal coping techniques including yoga, meditation, and family support. Workload and stress levels are positively correlated, according to statistics, highlighting the critical need for immediate and effective workplace changes. In order to create healthier and more inclusive workplaces, the research highlights the significance of policies that are attentive to gender dynamics, flexible work arrangements, and easily available mental health support networks for working women. These factors contribute to their well-being and productivity.